MENINGKATKAN KETERAMPILAN PADA ANAK TUNAGRAHITA RINGAN: STRATEGI PENINGKATAN KEMAMPUAN MOTORIK KASAR - Madhani, Adam Satriyo Putra; Mochammad Nursalim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to discuss improving gross motor skills in children with Mild Mental Disabilities. This study uses the Literature Review study method, where the author looks for references from previous studies, articles, journals or various other literature sources according to the title or topic to be discussed. The results of literature studies in various sources show that, Children with mild mental disabilities have intellectual abilities below children in general but can still be trained. Development in several aspects makes children with mental disabilities experience delays, one of which is the gross motor aspect in children so that they need interesting activities for children to be interested in following them. The conclusion of this study is that successful collaboration between parents, class teachers and therapists in handling and guiding children with Mild Mental Disabilities on an ongoing basis can help improve children's motor skills.